Exergia e serviços ecossistêmicos de duas bacias hidrográficas do estado de São Paulo, Brasil - Periotto, Natalia Andricioli (2016)
Eco-exergy is an innovative approach to evaluate ecosystem services, since it encompasses all possible ecosystem functions and processes in a single estimate. In this study, eco-exergy values of wetlands and native vegetation areas of Jacaré-Guaçu and Jacaré-Pepira Watersheds were estimated. The obtained values (average of 3,389 GJ.ha.ano-1, wetlands; average of 5,810 GJ.ha.ano- 1, native vegetation) are consistent with reference values showed by Jørgensen [Jørgensen, S.E. 2010. Ecosystem services, sustainability and thermodynamic indicators. Ecological Complexity, vol. 7, p. 311-313]. From a perspective of the ecoexergy concept, management practices of native vegetation and wetlands in both watersheds should consider not only quantity of vegetation conserved or restored, but also biodiversity of vegetation species. Consequently, multiple ecosystems services would be guaranteed for human well-being and for selfregulation of these ecosystems.